FREE SOFTWARE COMMUNITIES OF COSTA RICA - Flores, Sofía (2013)
The free software communities of Costa Rica have been investigated between 2006-2008. To understand their structure and functioning we keep a participant observation and conduct an electronic poll and interviews. The results are analyzed under the virtual community concept. They consist of strategic users, with scarce female involvement, ephemeral proposals, a touch of elitism and share a dialogic discourse.